Ocular trauma in the pediatric age group: a systematic review - Emine Özdemir Kaçer; İlker Kaçer (SpringerOpen, 2022)
Abstract Background Ocular traumas are the leading cause of acquired unilateral blindness in the pediatric age group. The aim of this study is to determine the incidence of pediatric ocular injuries, the etiological factors that cause them, and to make some preventive recommendations. Methods This was a retrospective observational study of pediatric ocular trauma (age < 18 years) presented to the pediatric emergency unit of our tertiary university hospital between January 2016 and December 2020. Demographic data such as age, gender, season, duration of admission, trauma etiology, and type of injury were recorded. Patients with missing medical records were excluded from the study. Results Two hundred two patients aged a mean of 107.4 ± 40.7 months including 87 females (43.07%) and 115 males (56.93%) were included in the study. Most of the patients (n = 135, 66.83%) were in the 7-11 years of age group. The vast majority of the study population lived in the urban area (n = 119, 58.91%). Most injuries were seen in the summer (n = 108, 53.47%). 59.41% of all patients had closed globe injuries. Hyphema (32.5%) and endophthalmitis (26.6%) were the most common in closed globe injuries. Of the open globe injuries, 39 were penetrating (47.5%), 12 were perforated (14.6%), and 23 were intraocular foreign body injuries (28%). It was determined that the places where the injury occurred were mostly in situations where family control was reduced, such as weddings, holidays, and playgrounds (80.69%). The most common causes of injury were toy guns (35.15%), stones (28.71%), and fireworks (16.34%). Conclusion This analysis is the first study to provide data on childhood ocular trauma in Aksaray. Most of the childhood ocular injuries can be prevented with simple precautions. For this purpose, effective and preventive strategies should be developed such as raising public awareness, providing parental control, and early intervention.